2016
DOI: 10.1080/09687599.2016.1223606
|View full text |Cite
|
Sign up to set email alerts
|

Physical environments and community reintegration post stroke: qualitative insights from stroke clubs

Abstract: This study investigated the environment's role in community reintegration amongst persons with experience of stroke. Focus group discussions with 29 individuals recruited from community stroke clubs in Scotland revealed that stroke influenced a person's perceptions, experience, use and enjoyment of the environment. Multiple specific (e.g. theatres, cafes) and more general (out-of-thehome) environments appeared capable of supporting community reintegration, providing settings in which individuals were able and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Particular difficulties were encountered when seeking to recruit stroke survivors and people with dementia. Future research could adopt alternative recruitment strategies such as, where appropriate, engaging with peer-support groups—see a study by Brookfield and Mead (2016) where participants with experience of stroke were successfully recruited through stroke clubs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particular difficulties were encountered when seeking to recruit stroke survivors and people with dementia. Future research could adopt alternative recruitment strategies such as, where appropriate, engaging with peer-support groups—see a study by Brookfield and Mead (2016) where participants with experience of stroke were successfully recruited through stroke clubs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first author, assisted by the third author, acted as the focus group moderator. Focus groups have been employed in research with older people [ 23 ], stroke survivors [ 24 , 25 ] and people with dementia [ 26 ] while the advantages and limitations of the method are well documented [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke is associated with physical, emotional and social consequences that affect an individual's quality of life [3][4][5]. Individuals with stroke aim to return to active living and reintegrate into society [6]. The conventional approach to stroke recovery is the delivery of rehabilitation services based on the medical principles of cure [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study on international physical therapists showed that patients lack motivation and priority to undertake the physical activity given to them by healthcare professionals were barriers to integrating physical exercise in the healthcare system (Soundy, Stubbs, Probst et al, 2014;Firth, Rosenbaum, Stubbs et al, 2016). A systematic review conducted on six qualitative articles stated that environmental factors (access, transport, and cost), health problems, unfavourable activities, confusion, and fear of failure were barriers to physical exercise (Brookfield & Mead, 2016). Other studies indicate strong and positive associations between the built environment and physical exercise participation (Henderson, Grode, O'Connell, & Schwartz, 2015;Oyeyemi, Adewale, Sandra et al, 2016).…”
Section: Introductionmentioning
confidence: 99%